Associations Between Brominated Flame Retardant Exposure and Depression in Adults: A Cross-Sectional Study - Yulan Cheng; Yue Fei; Zemin Xu; Ruiyao Huang; Yuling Jiang; Lihan Sun; Xuehai Wang; Shali Yu; Yonghua Luo; Xiaobo Mao; Xinyuan Zhao (Toxics, 2024)
Background: Brominated flame retardants (BFRs) are a type of widespread pollutant that can be transmitted through particulate matter, such as dust in the air, and have been associated with various adverse health effects, such as diabetes, metabolic syndrome, and cardiovascular disease. However, there is limited research on the link between exposure to mixtures of BFRs and depression in the general population. Methods: To analyze the association between exposure to BFRs and depression in the population, nationally representative data from the National Health and Nutrition Examination Survey (NHANES; 2005–2016) were used. In the final analysis, a total of 8138 adults aged 20 years and older were included. To investigate the potential relationship between BFRs and outcomes, we used binary logistic regression, restricted cubic spline (RCS), quantile-based g computation (QGC), and weighted quantile sum (WQS) regression. Results: The findings showed that serum BFR concentrations were associated with depressive symptoms over a broad spectrum. Binary logistic regression and RCS analysis showed that certain BFRs, particularly PBB153, were significantly and positively associated with the incidence of depression, even after adjustment for various confounders (p < 0.05). Mixed exposure to BFRs was also found to be associated with depression in the population, with a stronger association in men. The two most influential BFRs, PBB153 and PBDE85, were identified in both mixed exposure models and are potential risk factors of concern. Conclusion: Our study identified new insights into the relationship between BFRs and depression, but sizable population-based cohort studies and toxicology mechanism studies will be needed to establish causality.